Health care needs assessment of elderly with functional disability in Palam village of Delhi - Kumar, Devendra; Rasania, S. K.; Das, Ranjan (International Journal Of Community Medicine And Public Health, 2019)
Background: Exploring the health care needs of the aged is important in any society. Certain assessments of the elderly are comprehensive in that they are able to measure the met and unmet physical, mental and social needs in this population group and thus lead to overall improvement in their care as well as assistance for their health care providers. The objective of the present study was to assess the health care needs in elderly having functional disability in Palam village of Delhi. Methods: Health care needs assessment was done using CANE questionnaire in 81 elderly who were found to be functionally disabled out of the total 350 study subjects. It comprised of 24 items and two items related to caregivers need. Kappa test was applied to check for the inter rater agreement between the study subject and their caregivers. Results: Varied range of agreement was observed on most of the items, highest agreement noted for accommodation (98.7%) and lowest for intimate relationships (50.6%). Conclusions: Appropriate social and economic policies need to be made to mitigate the ill effects of ageing which should also address their health care needs.